PERAN LITERASI RISIKO SYARIAH DAN EFIKASI DIRI DIGITAL DALAM PENCEGAHAN PINJAMAN ONLINE ILEGAL - Evriyenni; Azimah Dianah; Amrie, Intan Safayana (Journal of Sharia Economics, 2026)
The rapid expansion of digital financial technology has significantly accelerated the adoption of online lending services in Indonesia. Alongside these advancements, however, there has been a concerning proliferation of illegal online lending platforms, including those falsely claiming compliance with sharia principles. This trend reflects a persistent gap in public understanding of sharia-related financial risks, as well as limited individual capacity to critically evaluate the security and legitimacy of digital financial services. This study investigates the role of sharia risk literacy and digital self-efficacy in mitigating engagement with illegal online lending among students of the Faculty of Economics and Islamic Business at Ar-Raniry State Islamic University, Banda Aceh. Employing a quantitative approach, the research examines how cognitive competence and individual belief systems influence prudent financial decision-making in accordance with sharia principles within a digital context. The findings are expected to demonstrate that higher levels of sharia risk literacy and digital self-efficacy significantly contribute to safer financial behavior and reduce vulnerability to fraudulent lending practices. Theoretically, this study enriches the discourse on Islamic financial literacy by integrating behavioral and cognitive dimensions. Practically, it offers strategic insights for regulators, higher education institutions, and Islamic fintech developers to design more effective educational interventions and regulatory frameworks aimed at preventing illegal online lending in the digital economy